2007
DOI: 10.1152/ajplung.00208.2006
|View full text |Cite
|
Sign up to set email alerts
|

Nonhematopoietic NADPH oxidase regulation of lung eosinophilia and airway hyperresponsiveness in experimentally induced asthma

Abstract: Cook-Mills JM. Nonhematopoietic NADPH oxidase regulation of lung eosinophilia and airway hyperresponsiveness in experimentally induced asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
95
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(108 citation statements)
references
References 78 publications
13
95
0
Order By: Relevance
“…These data are consistent with our previous reports that in vitro, endothelial cell PTP1B is a mediator of VCAM-1 signaling (16) and reports that VCAM-1 is required for infiltration of eosinophils in response to OVA challenge to the lung (12). This is also consistent with our previous report in which chimeric mice with a deficiency in nonhematopoietic NADPH oxidase 2 (NOX2), a VCAM-1 signal upstream of PTP1B, had accumulation of eosinophils on the endothelium and reduced eosinophils in the lung without altering lung adhesion molecules, cytokines, or chemokines (4).…”
Section: L246supporting
confidence: 92%
“…These data are consistent with our previous reports that in vitro, endothelial cell PTP1B is a mediator of VCAM-1 signaling (16) and reports that VCAM-1 is required for infiltration of eosinophils in response to OVA challenge to the lung (12). This is also consistent with our previous report in which chimeric mice with a deficiency in nonhematopoietic NADPH oxidase 2 (NOX2), a VCAM-1 signal upstream of PTP1B, had accumulation of eosinophils on the endothelium and reduced eosinophils in the lung without altering lung adhesion molecules, cytokines, or chemokines (4).…”
Section: L246supporting
confidence: 92%
“…In summary, VCAM-1-D6 Ab, which is reactive to VCAM-1 domain 6, inhibits transmigration but not adhesion, suggesting that the sixth IgG-like domain may participate in transmigration (36,50).…”
Section: Discussionmentioning
confidence: 89%
“…Leukocyte binding to adhesion molecules, including VCAM-1, activates signals within endothelial cells that allow the opening of narrow vascular passageways between endothelial cells or through an individual endothelial cell for transendothelial migration (34)(35)(36)(37)(38)(39). When endothelial cell adhesion molecule signaling is inhibited, leukocytes bind to the endothelium, but transendothelial migration does not occur (40), and leukocytes are often released from the endothelium to continue in the blood flow (41,42).…”
mentioning
confidence: 99%
“…For example, infection of gp91phox−/− mice with the yeast C. neoformans or with influenza virus was in either case found to result in increased Th1-skewed inflammation and granuloma formation, compared to their wild-type counterparts, which led to increased influenza clearance and protection against C. neoformans infection (204,205). Studies using chimera of gp91phox−/− mice indicated a contribution of non-hemapoetic cell NADPH oxidase to development of airways eosinophilia in a mouse model of allergic inflammation, suggesting a role for NOX2 within the vascular endothelium (206). Studies with gp91phox−/− mice also indicated a role for NOX2, presumbly within the endothelium, in development of pulmonary arterial hypertension in response to chronic hypoxia (176).…”
Section: Nox2mentioning
confidence: 99%